2014
DOI: 10.4236/ijcce.2014.32003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Governing Reactions in Coal Oxidation at Temperatures up to 400°C

Abstract: The present study aims to further understanding of the principal reactions that occur during coal oxidation at moderate temperatures. Mass change and heat evolution of a sample were monitored by thermo-gravimetric analysis coupled with differential thermal analysis (TGA/DTA). Gaseous and solid products were traced using online or in situ Fourier transform infrared spectroscopy (FTIR). Measurements were conducted by heating the samples up to 400˚C, with the O 2 concentration in the reaction medium set at 0, 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 18 publications
3
7
0
1
Order By: Relevance
“…All the TG/DTG profiles are available in the Supplementary Information (Figure S1). Zhan et al (2014) reported TG results for coal oxidation in dynamic runs up to 400 C and a similar trend for the mass change was observed. In that study, the sample mass under oxidation conditions increased up to 275 C and then decreased by increasing temperature.…”
Section: Thermogravimetric Analysissupporting
confidence: 67%
See 1 more Smart Citation
“…All the TG/DTG profiles are available in the Supplementary Information (Figure S1). Zhan et al (2014) reported TG results for coal oxidation in dynamic runs up to 400 C and a similar trend for the mass change was observed. In that study, the sample mass under oxidation conditions increased up to 275 C and then decreased by increasing temperature.…”
Section: Thermogravimetric Analysissupporting
confidence: 67%
“…In that study, the sample mass under oxidation conditions increased up to 275 C and then decreased by increasing temperature. The oxidation mechanism might be described as two parallel steps (Su et al, 2017): (1) char is directly oxidized to volatile products (CO 2 , CO and H 2 O) or (2) it initially reacts to form intermediate surface species, which subsequently either continue to react to gases or alternatively are stabilized as functionalized groups (hydroxyl and phenolic (eOH), carbonyl (eCO), carboxyl (eCOOH) and ether (CeOeC) linkages (Zhan et al, 2014)). The mass gain during oxidation is attributed to oxygen uptake and the formation of solid oxygenated complexes (Zhan et al, 2014).…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Bazı kömürlerin kendiliğinden yanmaya çok yatkın olduğu ve bazılarının ise olmadığı, hatta bazı damaların tavanının yandığı fakat tabanının yanmadığı olaylar bilinmektedir. Bunun nedeni, kömürde oksidasyonu başlatan temel parametrenin henüz tam olarak tespit edilememesidir [13], [14]. Kömürde oksidasyon ve kendiliğinden yanmaya etki eden faktörleri iki ana başlık altında toplamak mümkündür.…”
Section: Kömürün Kendiliğinden Yanma Mekanizması Ve Etki Eden Faktörlerunclassified
“…In [26][27][28], researchers examined the role of flow dynamics on the spontaneous combustion within an open stockpile using CFD simulations. In addition, other researchers have also studied the oxidation process and gaseous products under oxygen-lean conditions at low temperatures [29][30][31]. Note that the process of coal spontaneous combustion consists of oxygen absorption, mass weight gain/loss, oxidation, burn-off and finally coal combustion at high temperatures (>400 o C).…”
Section: Introductionmentioning
confidence: 99%
“…Note that the process of coal spontaneous combustion consists of oxygen absorption, mass weight gain/loss, oxidation, burn-off and finally coal combustion at high temperatures (>400 o C). Zhan et al [31] proposed four stages of coal oxidation, namely water evaporation, oxygen chemisorption, significant decomposition reaction reactions and burn-off reaction, taking place up to 400 o C as determined by a TG/DTA data. Wang [21] brought forward three stages as slow oxidation stage (< 70 o C) , accelerated oxidation stage (> 140 o C) and middle stage between them at low temperature coal oxidation .…”
Section: Introductionmentioning
confidence: 99%